Identification of the Selenoprotein S Positive UGA Recoding (SPUR) element and its position-dependent activity. Issue 12 (2nd December 2019) - Cockman, Eric M.; Narayan, Vivek; Willard, Belinda; Shetty, Sumangala P.; Copeland, Paul R.; Driscoll, Donna M.
ABSTRACT: Selenoproteins are a unique class of proteins that contain the 21 st amino acid, selenocysteine (Sec). Addition of Sec into a protein is achieved by recoding of the UGA stop codon. All 25 mammalian selenoprotein mRNAs possess a 3′ UTR stem-loop structure, the Selenocysteine Insertion Sequence (SECIS), which is required for Sec incorporation. It is widely believed that the SECIS is the major RNA element that controls Sec insertion, however recent findings in our lab suggest otherwise for Selenoprotein S (SelS). Here we report that the first 91 nucleotides of the SelS 3′ UTR contain a proximal stem loop (PSL) and a conserved sequence we have named the SelS Positive UGA Recoding (SPUR) element. We developed a SelS-V5/UGA surrogate assay for UGA recoding, which was validated by mass spectrometry to be an accurate measure of Sec incorporation in cells. Using this assay, we show that point mutations in the SPUR element greatly reduce recoding in the reporter; thus, the SPUR is required for readthrough of the UGA-Sec codon. In contrast, deletion of the PSL increased Sec incorporation. This effect was reversed when the PSL was replaced with other stem-loops or an unstructured sequence, suggesting that the PSL does not play an active role in Sec insertion. Additional studies revealed that the position of the SPUR relative to the UGA-Sec codon is important for optimal UGA recoding. Our identification of the SPUR element in the SelS 3′ UTR reveals a more complex regulation of Sec incorporation than previously realized.